Improving discovery rate in device-to-device (D2D) communications Using Power control technique - Asaad, Essam Mohammad; Alsalem, AbdAlkareem (Journal of engineering sciences and information technology, 2022)
The study focuses on the issue of choosing the best D2D pairs, which helps in increasing the number of pairs and reduces the burden of congestion on the cellular station, as the reuse of the frequency spectrum is one of the main challenges facing device-to-device communications, especially the issue of choosing D2D pairs with minimal interference and better Quality of Service QoS guarantee.A cell is designed with randomly distributed devices and choosing D2D pairs that can communicate with securing an appropriate QoS using an algorithm based on resource reuse so that each DUE has an overlap on each other, and then using the power control algorithm with the D2D connection pair selection algorithm through Making the transmission capacity between cellular devices connected to the D2D technology proportional to the distance between them in a way that ensures the quality of communication without the need to raise the capacity to avoid interference with neighboring links, whether D2D or cellular links.In order to reduce interference, this technology provides an increase in the value of SINR and an increase in the probability of meeting the appropriate conditions for establishing a D2D connection, thus freeing cell resources and increasing the quality of service.
Keywords: Quality of Service; Peer Discovery; Device-to-Device Communications; Interference